2019
DOI: 10.1021/acscatal.9b03066
|View full text |Cite
|
Sign up to set email alerts
|

Strategies To Improve the Activity While Maintaining the Selectivity of Oxidative Coupling of Methane at La2O3: A Density Functional Theory Study

Abstract: Oxidative coupling of methane (OCM) holds the promise to achieve high-value-added products directly from methane, and the strategies to improve the catalytic performance of this process are highly desired. In this work, we performed extensive density functional theory (DFT) calculations to systematically study the activity and selectivity of the OCM reactions on several types of the La 2 O 3 and CeO 2 catalysts. We theoretically evidenced that the La 2 O 3 catalyst has high hydrocarbon selectivity but low acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 68 publications
0
34
0
1
Order By: Relevance
“…Recently, we have systematically investigated the OCM reaction processes over La 2 O 3 and CeO 2 using DFT calculations. 20 Owing to their different surface geometric and electronic structures, La 2 O 3 and CeO 2 can promote different transformation pathways of the as-generated methyl species, following the first C−H bond breaking. The calculated results suggest that promoting the direct formation of CH 3…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have systematically investigated the OCM reaction processes over La 2 O 3 and CeO 2 using DFT calculations. 20 Owing to their different surface geometric and electronic structures, La 2 O 3 and CeO 2 can promote different transformation pathways of the as-generated methyl species, following the first C−H bond breaking. The calculated results suggest that promoting the direct formation of CH 3…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…• while the surface reducibility was also used as a descriptor for their catalytic characteristics. 20,23 However, in experimental studies, identifying the intrinsic activity of metal oxides in methane activation is still challenging because very few in situ techniques can be used to quantitatively detect CH 3…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that La 2 O 3 surfaces allow oxygen to be present as various anion species, (some of) which are highly active for methane activation [22,23] . Moreover, La 2 O 3 has been frequently coupled with Sr and Ce, [24–27] which is likely consistent with the observed importance of basic oxide‐forming elements. At 900 °C, high performing catalysts often contained both basic oxide‐forming elements and early transition metals as active elements (Figure 1c, d).…”
Section: Resultsmentioning
confidence: 63%
“…Numerous catalysts have been studied for the production of alkenes (C 2+ ) through the OCM process. The summary of various catalysts used in OCM for alkenes is presented in Table . …”
Section: Natural Gas Flaring Utilization Technologiesmentioning
confidence: 99%